Marszalkowie sejmow I Rzeczypospolitej - Olszewski, Henryk; Sieradzki, Wojciech; Kotowicz, Jaroslaw; Walukiewicz-Wolfram, Jolanta (Warszawa : Wydawn. Sejmowe, 1993)
Biographies of the numerous Marshals of the Seym of the First Polish Commonwealth.
Title on added t.p.: Marshals of the Seyms of the First Polish Commonwealth.
Summary in English.
Includes bibliographical references (p. 24-[27]) and index.
Keywords: Poland. -- Sejm -- Presiding officers -- Biography -- Portraits; Poland -- Biography -- Portraits